The mechanism of alpha lipoic acid on reducing the mda level and mcp-1 expression in endothelial dysfunction of hypercholesterolemia rat (rattus norvegicus) model - Sari, Dewi Perwito; Susilo, Imam; Khotib, Junaidi (Folia Medica Indonesiana, 2017)
Endothelial dysfunction is an initial condition of atherosclerosis and other vascular diseases where one of the risk factors is hypercholesterolemia. Blood cholesterol levels is associated with an increase in the production of reactive oxygen species (ROS). The increasing of ROS production can cause increased oxidative stress which in turn resulting in endothelial dysfunction. Alpha lipoic acid (ALA) is one of the antioxidant compound that has been developed and studied. In this study we found that the use of ALA in Rattus norvegicus rats signifficantly lower the total cholesterol levels at dose 60 mg/kgBW (p=0.020). ALA also inhibit the expression of Monocyte Chemoattractant Protein-1 (MCP-1) at dose 60 mg/kgBW (p=0.044) and reduces the formation of Malondialdehyde (MDA) at dose 120 mg/kgBW (p=0.009), which is the initial stage of the atherogenic development and prognosis of events, thus, ALA can reduce the risk of further damage to the endothelium.